Turks in Germany: An Evaluation of Socioeconomic Integration - Lodigiani, Mary (Colloquium: The Political Science Journal of Boston College, 2018)
This research evaluates the socioeconomic integration of those with Turkish heritage living in Germany. Although Turks first arrived in Germany just after World War II, their socioeconomic integration continues today. This research evaluates the structure of the German labor market, the education system, and language gap, and determines their roles in the discrimination against Germans with Turkish heritage. Personal accounts are also included to illustrate the struggles Turkish immigrants have faced over the years due to both cultural and economic factors. This paper challenges Germany to reexamine its socalled “welcome culture,” or “Wilkommenskultur,” as they reflect on their treatment of Turkish immigrants and plan for their future after Chancellor Merkel’s recent re-election.